2014
DOI: 10.3382/ps.2014-04092
|View full text |Cite
|
Sign up to set email alerts
|

Feather corticosterone evaluated by ELISA in broilers: A potential tool to evaluate broiler welfare

Abstract: The measure of corticosterone (CORT) in feathers has been recently recognized as a valid and easily obtainable measure of chronic glucocorticoids secretion in avian species. This measure provides meaningful interpretations of how individuals respond to environmental perturbations. The growing interest of the public toward animal-food production welfare shows the need for improving and expanding objective tools to evaluate this issue. The present study evaluates whether it is possible to detect CORT in broiler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 12 publications
6
37
1
Order By: Relevance
“…CORT concentrations in breeding and non-breeding feathers (P1 and S13, respectively) were assessed through competitive EIA kits (Corticosterone ELISA kit; Neogen â Corporation, Ayr, UK), following an optimized protocol described elsewhere (Carbajal et al 2014). Briefly, after discarding the calamus (Bortolotti et al 2008), feathers were minced with a ball-mill (Retsch â , MM2 type, Haan, Germany) for 5 min at 25 Hz.…”
Section: Corticosterone Determinationmentioning
confidence: 99%
“…CORT concentrations in breeding and non-breeding feathers (P1 and S13, respectively) were assessed through competitive EIA kits (Corticosterone ELISA kit; Neogen â Corporation, Ayr, UK), following an optimized protocol described elsewhere (Carbajal et al 2014). Briefly, after discarding the calamus (Bortolotti et al 2008), feathers were minced with a ball-mill (Retsch â , MM2 type, Haan, Germany) for 5 min at 25 Hz.…”
Section: Corticosterone Determinationmentioning
confidence: 99%
“…Previous studies have reported similar observations. Feather CORT concentrations were unrelated to sex in house sparrows (Passer domesticus; Koren et al, 2012), red-legged partridge (Alectoris rufa; Bortolotti et al, 2008) or the broiler (Gallus gallus domesticus; Carbajal et al, 2014). The limited data available suggests that feather CORT concentrations discriminate or diverge most effectively when high, stress-or implant-induced, levels of CORT are present in the blood (Fairhurst et al, 2013;Lattin et al, 2011).…”
Section: Intra-specific Variation In Feather Corticosterone Concentramentioning
confidence: 99%
“…Bourgeon et al, 2014;Carbajal et al, 2014;Sepp et al, 2014) but these are in the minority. Concentrations of CORT in feathers have been shown to vary in response to life history events (Bortolotti et al, 2008;Crossin et al, 2013), sibling competition (Yosef et al, 2013), health status (Harriman et al, 2014;Meitern et al, 2013;Mougeot et al, 2010;Sild et al, 2014), overwinter survival (Koren et al, 2012), food limitation , reproductive investment (Fairhurst et al, 2012a;Kouwenberg et al, 2013), and with environmental conditions (Carrete et al, 2013;Fairhurst et al, 2011;Fairhurst et al, 2012b;Legagneux et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In laying hens, the condition of the plumage and the integument acts as an indicator for feather pecking and cannibalism, both being behavioral disorders caused by various challenges the birds had or have to cope with ( Sepeur et al., 2015 ; Giersberg et al., 2017 ). Recent studies showed that the evaluation of animal welfare in birds may be carried out objectively and noninvasively with the measurement of the stress-related hormone corticosterone in feathers ( Bortolotti et al., 2008 ; Bortolotti et al., 2009 ; Fairhurst et al., 2011 ; Carbajal et al., 2014 ; Ganz et al., 2018 ; Johns et al., 2018 ; Weimer et al., 2018 ; Alba et al., 2019 ; von Eugen et al., 2019 ; Nordquist et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%